Performance Analysis of OLSR in both UDP and TCP environment - Sahu, Diganto; Barman, Utpal (International Journal of Computer Sciences and Engineering, 2025)
In this paper we have discussed about advanced version of Link State Protocol i.e. OLSR (Optimized Link State Protocol. OLSR is a Proactive routing protocol which mainly can be used for dense network because of its nature to reduce the retransmission of packets substantially. Here we have seen how the performance of OLSR protocol varies when number of nodes are changed and how it perform when the speed of nodes changes with change of pause time interval of fixed position. The discussion is based on graph of 2 dimensions in both TCP and UDP environment where the performance metrics are on x-axis, and number of node and node mobility are on y-axis (Abstract)